2005
DOI: 10.1681/asn.2004110944
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Impaired Urinary Concentrating Ability in Glucocorticoid-Deficient Rats

Abstract: The purpose of this study was to examine urinary concentrating ability and protein expression of renal aquaporins and ion transporters in glucocorticoid-deficient (GD) rats in response to water deprivation as compared with control rats. Rats underwent bilateral adrenalectomies, followed only by aldosterone replacement (GD) or both aldosterone and dexamethasone replacement (control). As compared with control rats, the GD rats demonstrated a decrease in cardiac output and mean arterial pressure. In response to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
(24 reference statements)
2
29
0
Order By: Relevance
“…32 One postnatal study in adrenalectomized adult rats showed a decrease in mean BP and cardiac output in rats that received only mineralocorticoid replacement compared with controls that received both mineralocorticoid and GC replacement. 33 Interestingly, these same rats demonstrated an impairment in urinary concentrating ability with decreased expression of aquaporin-2 and impaired countercurrent multiplication, 33 so it is difficult to sort out the effects of GC deficiency versus volume deficiency. Overall, it is unclear whether GC increase or decrease cardiac output; they may have both effects in particular settings.…”
Section: Discussionmentioning
confidence: 99%
“…32 One postnatal study in adrenalectomized adult rats showed a decrease in mean BP and cardiac output in rats that received only mineralocorticoid replacement compared with controls that received both mineralocorticoid and GC replacement. 33 Interestingly, these same rats demonstrated an impairment in urinary concentrating ability with decreased expression of aquaporin-2 and impaired countercurrent multiplication, 33 so it is difficult to sort out the effects of GC deficiency versus volume deficiency. Overall, it is unclear whether GC increase or decrease cardiac output; they may have both effects in particular settings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a V2 receptor antagonist has been shown in this rat model of hypothyroidism to reverse the increased AQP2 and the impaired response to an acute water load (Figure 4) (44). The hypothyroid rats also demonstrated a diminution in maximal urinary concentration which was associated with a defect in the counter-current concentrating mechanism (45). This defect was related to diminished maximal medullary osmolality and down-regulation of the cotransporter, NA-K-2Cl, which initiates the counter-current concentrating mechanism.…”
Section: Hypo-and Hyperthyroidismmentioning
confidence: 79%
“…In contrast, glucocorticoid deficiency is, if anything, mildly sodium retaining. A decrease in blood pressure, however, occurs secondary to diminished cardiac output and an impaired systemic vascular response to hypotension (53). The hyponatremia of hypopituitarism, i.e., selective glucocorticoid deficiency, can be reversed with physiological doses of hydrocortisone (54).…”
Section: Glucocorticoid Deficiency and Mineralocorticoid Deficiencymentioning
confidence: 99%
“…2 Experimental glucocorticoid deficiency also exhibited impaired maximal urinary concentration, which was associated with a downregulation of AQP2. 3 The role of the excessive glucocorticoid hormone, as occurs with Cushing syndrome, is also known to be associated with alteration in body water homeostasis, but the molecular mechanisms have not been studied. It has been shown, however, that patients as well as experimental animals demonstrated polyuria in the presence of excess of glucocorticoid hormone.…”
mentioning
confidence: 99%